2008
DOI: 10.1243/09544089jpme163
|View full text |Cite
|
Sign up to set email alerts
|

An experimental evaluation of induction bending as a method for producing pipe bends with radii ≥2.5D

Abstract: This paper briefly describes induction bending and highlights some of the challenges associated with this technique in the production of tight bends in thick-walled pipe. The authors then go on to describe how data obtained from production runs and specifically commissioned trial bends were used to examine the factors believed to influence the generation of adverse geometry during bending, and to determine the relative importance of each factor.The paper concludes by examining previously published empirically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Tube (pipe) bending using local induction heating is an advanced process that is used to bend thick-walled pipes with small bending radii and large diameters (74)(75)(76)(77). It is cost effective and has been widely used in many fields such as power, transportation, and chemical industries since it was invented by Dai-ichi High Frequency Co. (DHF0 of Japan); Figure 40 shows the bending principle of induction tube bending.…”
Section: Local Induction Heat Tube Bendingmentioning
confidence: 99%
See 1 more Smart Citation
“…Tube (pipe) bending using local induction heating is an advanced process that is used to bend thick-walled pipes with small bending radii and large diameters (74)(75)(76)(77). It is cost effective and has been widely used in many fields such as power, transportation, and chemical industries since it was invented by Dai-ichi High Frequency Co. (DHF0 of Japan); Figure 40 shows the bending principle of induction tube bending.…”
Section: Local Induction Heat Tube Bendingmentioning
confidence: 99%
“…The thinning and thickening ratio of the pipe wall thickness, the pushing force, the oval shape of the cross section of the pipe, and the springback after unloading were discussed. The literature (76,77) reported the challenges associated with induction bending in the production of tight bends in thick-walled pipe, and concluded that the existing charts are deficient when considering extrados wall thinning. The analytical models predicted the final deformed geometry of induction bends in thick-walled pipe, which was compared with the results of empirically derived charts and computational models.…”
Section: Local Induction Heat Tube Bendingmentioning
confidence: 99%
“…These problems are most apparent when producing tight bends (i.e. where the bend radius 2.5 × nominal pipe diameter) from thick-walled (>15 mm) pipe [1].…”
Section: Introductionmentioning
confidence: 99%
“…This paper is part of a suite of publications by the same authors [1][2][3][4], which together comprise an industrial study of temper-free (TF) induction bending of pipe. Previous work noted that as well as geometric problems, bending thick-walled superduplex pipe to tight radii can also result in a catastrophic deterioration in mechanical properties and corrosion resistance [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…A previous investigation by the authors considered methods of reducing the manufacturing costs of thickwalled (wall thickness nominal diameter/20) super duplex pipework featuring complex geometry, such as those used in the petrochemical, oil, and gas industries [2]. The form of induction bending of interest to the authors is temper-free (TF), a cost-effective variant where no post-bend heat treatment is used [3].…”
Section: Introductionmentioning
confidence: 99%